2013
DOI: 10.5539/ijef.v5n4p71
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of IFRS on the Value Relevance of Accounting Information: Evidence from Turkish Firms

Abstract: Value relevance is being defined as the ability of information disclosed by financial statements to capture and summarize firm value. Value relevance can be measured through the statistical relations between information presented by financial statements and stock market values or returns. In many studies, Ohlson model (1995) has been adopted to explore relationships among the market value of equity and two main financial reporting variables, namely the book value of equity per share (represents balance sheet) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
104
1
31

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(163 citation statements)
references
References 25 publications
14
104
1
31
Order By: Relevance
“…International studies, particularly in European countries, have examined this topic and have advanced the understanding of the effects of the adoption of IFRS on accounting information itself and on the users of that information (Ashbaugh & Pincus, 2001;Barth et al, 2008;Garanina & Kormiltseva, 2014;Kargin, 2013;Jarva & Lantto, 2012;Landsman, Maydew, & Thornock, 2012;Soderstrom & Sun, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…International studies, particularly in European countries, have examined this topic and have advanced the understanding of the effects of the adoption of IFRS on accounting information itself and on the users of that information (Ashbaugh & Pincus, 2001;Barth et al, 2008;Garanina & Kormiltseva, 2014;Kargin, 2013;Jarva & Lantto, 2012;Landsman, Maydew, & Thornock, 2012;Soderstrom & Sun, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing significance of financial report for international markets led to more research investigating the value relevance of accounting information in non-developed markets outside of the United States (Amir et al, 1993;Collins et al, 1997;Graham et al, 2000), which were extended to emerging markets (Chebaane & Othman, 2014;Chen et al, 2001;Kargin, 2013;Mironiuc et al, 2015;Umoren & Enang, 2015;Păşcan, 2015). The results of this literature on these emerging markets provided different findings on the relevance of accounting information with respect to local accounting standards and new accounting reporting standards for different countries and sectors.…”
Section: Introductionmentioning
confidence: 80%
“…In contrast, after the adoption of IFRS, earnings were found to be more value relevant than book value; however, a higher incremental value relevance of book value was reported for US GAAP users. Kargin (2013) explored the relationship of book value (balance sheet) and earnings (income statement) with a market value under two different accounting regimes from 1998 to 2011 for Turkish firms. They observed that book value improved during the period of IFRS adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Penelitian ini ingin melihat dampak adopsi IFRS pada satu jenis industri saja yaitu perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI), sehingga penelitian ini bertujuan menguji apakah adopsi IFRS yang telah dimulai secara bertahap pada tahun 2008 dapat meningkatkan kualitas informasi akuntansi pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI). Selain itu, penelitian ini menggunakan proksi yang sama dengan yang dilakukan oleh Liu dan Liu (2007), Barth et al (2008), Paananen dan Lin (2009), Kousenidis et al(2010), Kwong (2010), Outa (2011) Agostino et al (2011), dan Kargin (2013) yaitu kualitas informasi akuntansi diukur dengan proksi relevansi nilai (value relevance). Proksi ini digunakan sesuai dengan hasil penelitian yang dilakukan oleh Barth et al (2008) yang menyatakan informasi akuntansi yang berkualitas tinggi adalah informasi dengan tingkat relevansi nilai yang tinggi.…”
Section: International Financial Reporting Standards (Ifrs) Yang Sebeunclassified